Human gut microbiome impacts skeletal muscle mass via gut microbial synthesis of the short‐chain fatty acid butyrate among healthy menopausal women. Issue 6 (1st September 2021) - Lv, Wan‐Qiang; Lin, Xu; Shen, Hui; Liu, Hui‐Min; Qiu, Xiang; Li, Bo‐Yang; Shen, Wen‐Di; Ge, Chang‐Li; Lv, Feng‐Ye; Shen, Jie; Xiao, Hong‐Mei; Deng, Hong‐Wen
Abstract: Background: Increasing evidence suggests that human gut microbiome plays an important role in variation of skeletal muscle mass (SMM). However, specific causal mechanistic relationship of human gut microbiome with SMM remains largely unresolved. Understanding the causal mechanistic relationship may provide a basis for novel interventions for loss of SMM. This study investigated whether human gut microbiome has a causal effect on SMM among Chinese community‐dwelling healthy menopausal women. Methods: Estimated SMM was derived from whole‐body dual‐energy X‐ray absorptiometry. We performed integrated analyses on whole‐genome sequencing, shotgun metagenomic sequencing, and serum short‐chain fatty acids (SCFAs), as well as available host SMM measurements among community‐dwelling healthy menopausal women ( N  = 482). We combined the results with summary statistics from genome‐wide association analyses for human gut microbiome ( N  = 952) and SMM traits ( N  = 28 330). As a prerequisite for causality, we used a computational protocol that was proposed to measure correlations among gut metagenome, metabolome, and the host trait to investigate the relationship between human gut microbiome and SMM. Causal inference methods were applied to assess the potential causal effects of gut microbial features on SMM, through one‐sample and two‐sample Mendelian randomization (MR) analyses, respectively. Results: In metagenomic association analyses, the increased capacity for gut microbial synthesis of the SCFA butyrate was significantly associated with serum butyrate levels [Spearman correlation coefficient (SCC) = 0.13, P  = 0.02] and skeletal muscle index (SCC = 0.084, P  = 0.002). Of interest was the finding that two main butyrate‐producing bacterial species were both positively associated with the increased capacity for gut microbial synthesis of butyrate [ Faecalibacterium prausnitzii (SCC = 0.25, P  = 6.6 × 10 −7 ) and Butyricimonas virosa (SCC = 0.15, P  = 0.001)] and for skeletal muscle index [ F. prausnitzii (SCC = 0.16, P  = 6.2 × 10 −4 ) and B. virosa (SCC = 0.17, P  = 2.4 × 10 −4 )]. One‐sample MR results showed a causal effect between gut microbial synthesis of the SCFA butyrate and appendicular lean mass ( β  = 0.04, 95% confidence interval 0.029 to 0.051, P  = 0.003). Two‐sample MR results further confirmed the causal effect between gut microbial synthesis of the SCFA butyrate and appendicular lean mass ( β  = 0.06, 95% confidence interval 0 to 0.13, P  = 0.06). Conclusions: Our results may help the future development of novel intervention approaches for preventing or alleviating loss of SMM.